Pengaruh Konten Visual dan Storytelling pada Instagram dalam Meningkatkan Minat Kunjungan Konsumen ke Bendega Jimbaran - I Kadek Pasek Pastika Jaya; Putu Ratna Juwita Sari; Komang Sri Widiantari; Putu Ayu Titha Paramita Pika (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The post-pandemic recovery of the food and beverage industry has encouraged culinary businesses to intensify digital marketing strategies, particularly through social media platforms such as Instagram. However, limited empirical studies have specifically examined how Instagram-based visual content and storytelling influence consumers’ visit intention to culinary destinations. This study aims to analyze the effect of visual content and storytelling on consumers’ visit intention to Bendega Bali Jimbaran. A quantitative approach was employed by distributing structured questionnaires to 120 Instagram users who had viewed Bendega Bali Jimbaran’s Instagram content. The data were collected using purposive sampling and analyzed through multiple linear regression using SPSS. The results indicate that visual content has a positive and significant effect on visit intention (? = 0.490, p < 0.001), while storytelling also shows a positive and significant influence (? = 0.294, p < 0.001). Simultaneously, both variables significantly affect visit intention, with the model explaining 75% of the variance. These findings highlight the importance of integrating high-quality visual presentation and meaningful storytelling in Instagram marketing strategies to enhance consumers’ intention to visit culinary destinations.